Consumer willingness to pay for attributes of west-African poultry: using the microeconometrics of implicit price - (:unkn) unknown (My University, 2011)
Consumer concerns in food purchasing contain a number of attributes, including the nutritional and sanitary values, conditions of breeding and selling, and other social issues. The purpose of this paper is to introduce an analytical and an empirical approaches to estimating the marginal willingness to pay (WTP) for chicken attributes in Cameroon using data from an investigation on the field. First we constructed a theoretical model of implicit price. Secondly, we assumed that WTP for chicken attributes can be derived from estimate hedonic function, there by expressing the prices consumers are willing to pay as function of implicit price of each chicken attributes. Two models are proposed and discussed. Our findings indicate that in spite of the possibility of bargaining the price of the local flesh chicken, consumer’s substituted it by imported frozen cut chicken which main attributes are low cost, sold in separated parts and available in all urban markets.
Keywords: African Research